Old Town, Yellowknife, NT -- photograph ... - Seale, Linda N. (University of Alberta Library, 2012)
View of Old Town, Yellowknife, from the ice on Yellowknife Bay. Pilot's Monument at the top of the hill commemorates early bush pilots and also has a flashing light that warns if a small plane is about to land or take off in the channel between Old Town and Jolliffe Island. Photograph taken March 2012 ...